The Effect of Binahong Leaves (Anredera Cordifolia (Ten) Steenis) on Perineal Wound Healing Time in Postpartum Women at the Koncara Community Health Center in Purwakarta - Nurhayati, Nurhayati; Yola Dwi Putri , Febby (Jurnal Indonesia Sosial Sains, 2025)
Successful exclusive breastfeeding remains a challenge, especially for primiparous mothers. Perineal wounds are a common condition experienced by postpartum mothers due to vaginal delivery. Proper wound management is crucial to prevent infection and accelerate healing. Binahong leaves (Anredera cordifolia (Ten.) Steenis) are known to contain flavonoids, saponins, and ascorbic acid, which act as anti-inflammatory, antibacterial, and accelerate tissue regeneration. This study aims to determine the effect of binahong leaf administration on the duration of perineal wound healing in postpartum mothers at the Koncara Community Health Center in Purwakarta. The study used a quasi-experimental design with a post-test only control group. The sample consisted of 60 postpartum mothers (30 in the intervention group, 30 in the control group) taken using a purposive sampling technique. The results of the analysis using an independent t-test showed a significant difference in wound healing time between the intervention and control groups (p < 0.05). The average wound healing in the intervention group was faster (5.2 days) than the control group (7.1 days). Conclusion: Administering binahong leaves significantly accelerated perineal wound healing in postpartum mothers. Binahong leaves are recommended as a complementary therapy for perineal wound care.